Radiation attenuation by single‐crystal diamond windows. Issue 1 (23rd December 2016) - Guthrie, M.; Pruteanu, C. G.; Donnelly, M.-E.; Molaison, J. J.; dos Santos, A. M.; Loveday, J. S.; Boehler, R.; Tulk, C. A.
Abstract : This work describes a semi‐empirical attenuation correction that has been developed for neutron time‐of‐flight measurements with diamond‐anvil cells. Abstract : As artificial diamond becomes more cost effective it is likely to see increasing use as a window for sample environment equipment used in diffraction experiments. Such windows are particularly useful as they exhibit exceptional mechanical properties in addition to being highly transparent to both X‐ray and neutron radiation. A key application is in high‐pressure studies, where diamond anvil cells (DACs) are used to access extreme sample conditions. However, despite their utility, an important consideration when using single‐crystal diamond windows is their interaction with the incident beam. In particular, the Bragg condition will be satisfied for specific angles and wavelengths, leading to the appearance of diamond Bragg spots on the diffraction detectors but also, unavoidably, to loss of transmitted intensity of the beam that interacts with the sample. This effect can be particularly significant for energy‐dispersive measurements, for example, in time‐of‐flight neutron diffraction work using DACs. This article presents a semi‐empirical approach that can be used to correct for this effect, which is a prerequisite for the accurate determination of diffraction intensities.